Moss diversity in the state of Aguascalientes Mexico: Revision and update - Claudio Delgadillo-Moya; Ana Paola Peña-Retes (Botan‪ical Sciences, 2017)
Background: Seven moss species were known from the state of Aguascalientes before a study by Delgadillo et al. (2015) listed 38 new records for its moss flora.